Study of physio-mechanical properties of refractory fireclay for production of furnace lining - Job Ajala, Amkpa; Badarulzaman, Nur Azam (American Scientific Publishers, 2018)
This study focused on the Gombe fireclay that is under-utilized despite its abundance as essential ingredient for the manufacture of refractories. Hence, the clay was studied and appraised for its appropriateness for the manufacture of refractory fireclay brick. The physical, mechanical and thermal properties were investigated according to ASTM Standard Test Methods for fireclay refractories. Its chemical composition result indicated that it belongs to alumino-silicate group. Its refractoriness proved that it is a high duty (siliceous) refractory brick with refractoriness of 1621 °C equivalent to PCE Segar cone 26. It was sintered at varied sintering temperatures of 900 °C, 1000 °C, 1200 °C and 1100 °C. The sintering temperature of 1200 °C was found to be the best which significantly influenced the mechanical properties. The cold crushing strength was 15.37 MPa, apparent porosity was 24.52%, firing shrinkage was 7.5% and the bulk density was 1.9 g/cm3. The experimental result proved that the clay was suitable for production of refractory fireclay brick for furnace lining.